Viral and host factors regulating influenza virus replication - Nilsson, B (2017)
Avian influenza A viruses typically do not replicate very efficiently when exposed to a mammalian host species. One of the reasons for this is the low activity of the viral RNA-dependent RNA polymerase of avian influenza viruses in mammalian cells. This host restrictive effect can be overcome by adaptive mutations in the avian polymerase, many of which are found in the 627-domain of the PB2 polymerase subunit. Deletion of the 627-domain revealed that this domain is not required for enzymatic functions of the polymerase in vitro, but that it essential for viral replication in a cellular environment in a nucleoprotein-independent manner. While the 627-domain is not necessary for viral RNA synthesis, it was demonstrated that it is involved in mediating encapsidation of nascent replication products. Recently the host factor ANP32A was shown to be the main determinant of host range restriction of the viral polymerase. It was demonstrated that during viral infections ANP32A interacts with KPNA2, a host factor strongly linked to host range restriction of the viral polymerase. It was also revealed that avian polymerases specifically are restricted in vRNA synthesis, a defect that was reversed in the presence of avian ANP32A. ANP32A was shown to be an enhancer of vRNA synthesis in vitro. Viral polymerase-polymerase interactions have been reported previously and presumably fulfil several essential functions during viral replication. Here the potential interaction interfaces of two different polymerase dimers were investigated and a role of polymerase dimers in replication and in trans-activation of cRNA-bound polymerases was found. RNA-binding proteins are essential for RNA metabolism and therefore cell physiology. It has been reported that the RNA-binding proteome responds to biological stimuli. Here the response of the RNA-binding proteome to influenza virus infection was investigated using an in vivo UV crosslinking interactome capture technique. It was demonstrated that the RNA-binding proteome is significantly altered and that this effect is independent of protein abundance. Several host RNA-binding proteins were identified that change their RNA-binding behaviour and that could have pro- or antiviral functions during influenza virus infection.